Diet digestibility and rumen traits in response to feeding wed corn gluten feed and a pellet consisting of raw soybean hulls and corn steep liquor - Ferdinand, E. E.; Shirley, John E.; Titgemeyer, Evan C.; DeFrain, J.M.; Park, A.F.; Johnson, D.E.; Ethington, R.T. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four ruminally cannulated and two intact multiparous Holstein cows were used in a 3 × 3 replicated Latin square design to evaluate digestibility and rumen traits in lactating dairy cows in response to feeding wet corn gluten feed and a novel product containing raw soybean hulls and corn steep liquor. Three dietary treatments were fed in the experiment. The control contained (DM basis) 30% alfalfa hay, 15% corn silage, 32% corn, 9.3% whole cottonseed, 4.4% solvent soybean meal (SBM), 3.3% expeller SBM, 1.3% fish meal, 1% wet molasses, and 3.7% vitamins/ minerals. Wet corn gluten feed replaced 10% alfalfa hay, 5% corn silage, 5% corn grain, and expeller SBM replaced solvent SBM to maintain diet rumen undegradable protein. The novel product replaced 10% alfalfa hay, 5% corn silage, 3% solvent SBM, and 2% corn. Diets were analyzed to have dietary crude protein percentage and energy density values (Mcal/lb, NEL) of 18.7, 0.75; 18.7, 0.77; 18.7, 0.74; for control, wet corn gluten feed, and the novel product, respectively. Experimental periods were 14 days (10 days adaptation and 4 days collection). Acid insoluble ash was used to estimate fecal output. Dry matter intake averaged 37.9 lb/day and total tract digestibilities of dry matter (DM), organic matter, neutral detergent fiber (NDF), acid detergent fiber (ADF), and crude protein did not differ among diets: 71.7%, 73.2%, 63.1%, 58.5% and 73.0%, respectively. Diets affected liquid dilution rate, ruminal pH, and ruminal concentrations of total volatile fatty acids and ammonia similarly. The molar ratio of acetate to propionate was greater (P<0.05) for control (3.38) than for wet corn gluten feed (2.79) and the novel product (2.89). Inclusion of wet corn gluten feed and the novel product at 20% of dietary DM as a partial replacement for alfalfa hay, corn silage, corn grain, and SBM in diets fed to lactating dairy cattle supported lactational performance similar to the control diet. Additionally, combining wet corn gluten feed or the novel product with corn silage and alfalfa hay maintained milk fat yields and ruminal pH, thereby demonstrating that wet corn gluten feed and the novel product can serve as an effective source of fiber when fed at 20% of dietary DM. These results indicate that wet corn gluten feed and the novel product tested can serve as alternative feedstuffs in lactating dairy cattle diets.
Keywords: Dairy; Wet corn gluten feed; Soybean hulls; Corn steep liquor; By-product